Victimological apparatus for the study of intra-family violence (Journal of actual problems of jurisprudence, 2022)
The study of victims of domestic violence is an urgent issue. To eradicate intra-family violence, we must investigate not only the identity of the perpetrator, but also the identity of the victim, we must not forget. Since the victim and the perpetrator of intra-family violence have a close relationship and connections with each other.Analyzing victims of domestic violence, it is possible to classify them by age; gender; role status; moral and psychological characteristics; the severity of the crime from which the victim suffered; the degree of guilt of the victim; the nature of the victim's behavior. Persons at risk of being victims of domestic violence behave in different ways: aggressively or in another provocative way; passively, yield to violence; show a complete misunderstanding of the tricks of criminals or elementary carelessness.The conceptual basis of the victimological apparatus consists of such concepts as "victim" or "victim", "victimogenic factors", "victimization", "victim behavior", "victimization", "victimological situation", "victimological prevention".In order to prevent domestic violence, it is necessary to approve an anti-discrimination policy against women in society, introduce psychological assistance and rehabilitation programs for women in family crisis situations, as well as a system of psychological and practical measures aimed at correcting personal victim qualities and preventing victim behavior of women.Keywords: victimological apparatus, criminal personality, victim behavior, victim, family.